1983
DOI: 10.1901/jaba.1983.16-203
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Analysis of a Pedestrian Safety Training Program

Abstract: A previously developed and analyzed pedestrian safety training program was used to teach appropriate street-crossing behaviors to kindergarteners and first graders. Adult crossing guards were trained to provide pedestrian safety instruction. Trained observers monitored the quality of instructions given by crossing guards and the pedestrian behavior of young children as they crossed the street. A multiple-baseline analysis of the effects of two training programs indicated that guards were able to deliver the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…By shepherding children to cross when it is safe, they help children maintain their safety. They also serve as models, demonstrating safe behavior, providing praise for safe pedestrian behaviors, and correcting unsafe behaviors when needed 82. Research suggests crossing guards do not need to be professionals such as police officers or teachers.…”
Section: Preventionmentioning
confidence: 99%
See 3 more Smart Citations
“…By shepherding children to cross when it is safe, they help children maintain their safety. They also serve as models, demonstrating safe behavior, providing praise for safe pedestrian behaviors, and correcting unsafe behaviors when needed 82. Research suggests crossing guards do not need to be professionals such as police officers or teachers.…”
Section: Preventionmentioning
confidence: 99%
“…Research suggests crossing guards do not need to be professionals such as police officers or teachers. Instead, almost any mature pedestrian with some minimal training, including even older children or teenagers, can provide proper training and feedback to children 82,96…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have analyzed the effects of the individual components of BST, and have demonstrated the importance all four steps. In this line, Yeaton and Bailey ( 1983 ) applied a package to train guards about how to teach children to cross the street; they then analyzed the effectiveness of the different steps. They found that the rehearsal, feedback and praise components were necessary to produce effective behavioral change, while isolated components were not so effective.…”
Section: Introductionmentioning
confidence: 99%